STRATEGIC ENTREPRENEURSHIP: A CASE IN THE BRAZILIAN AUTOMOBILE INDUSTRY - Afonso Carneiro Lima; Edison Fernandes Polo; Fátima Regina Ney Matos (Future Studies Research Journal: Trends and Strategies, 2010)
This work addresses an entrepreneurial phenomenon of strategic administration within the automobile industry: the creation of the automaker Troller Veículos Especiais (TVE). The case study at hand is justified by the positioning of this company around two market niches and its relative success in an industry characterized by few and powerful players. Our aim was to analyze the entrepreneurial and strategic process of discovering opportunity, the analysis used for internal and external factors, and the adoption of its strategic positioning in exploring two automobile market niches: in the B2B market, vehicles adapted to specific operational functions; and in the B2C, off-road vehicles with a strong appeal to consumers’ life styles. This case study allowed us to visualize the challenging path of a genuinely Brazilian small company in a sector dominated by large multinational groups, besides demonstrating decision-related dilemmas and aspects related to managerial creativity. Key-words: Automobile industry. Case study. Strategic entrepreneurship. Discovery theory. Strategic positioning.